Editorial: The Need to Pay More Attention to Ethical Issues When Publishing in Scientific Journals - Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
This issue features 12 articles: six from Colombia, two from Mexico, one from Vietnam, one from Türkiye, one from Spain, and one international collaboration between Spain and Portugal. This attests to the incorporation of representative voices from different parts of the globe.